The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3389/falgy.2020.628381
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial-Mesenchymal Transition in Atopy: A Mini-Review

Abstract: Atopic diseases, particularly atopic dermatitis (AD), asthma, and allergic rhinitis (AR) share a common pathogenesis of inflammation and barrier dysfunction. Epithelial to mesenchymal transition (EMT) is a process where epithelial cells take on a migratory mesenchymal phenotype and is essential for normal tissue repair and signal through multiple inflammatory pathways. However, while links between EMT and both asthma and AR have been demonstrated, as we outline in this mini-review, the literature investigating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 135 publications
0
3
0
Order By: Relevance
“…This suggests alterations in the cell-cell adhesions, similar to other epithelia under inflammatory conditions [56,97]. The decreased expression of E-cadherin and the upregulation of another type of cadherin, P-cadherin, have been reported in psoriatic skin and dermatitis [98][99][100][101][102]. Changes in the cadherin function affect AJ integrity, the recruitment and activity of adaptor proteins, and therefore, the AJ-mediated mechanosignaling.…”
Section: Epidermal Cell-cell Adhesionsmentioning
confidence: 69%
“…This suggests alterations in the cell-cell adhesions, similar to other epithelia under inflammatory conditions [56,97]. The decreased expression of E-cadherin and the upregulation of another type of cadherin, P-cadherin, have been reported in psoriatic skin and dermatitis [98][99][100][101][102]. Changes in the cadherin function affect AJ integrity, the recruitment and activity of adaptor proteins, and therefore, the AJ-mediated mechanosignaling.…”
Section: Epidermal Cell-cell Adhesionsmentioning
confidence: 69%
“…S13D-F). Comparing the variant list with the RNAseq results indicated that genes which contained DNA variants and differentially expressed transcripts were led by the known modulator of NADPH metabolism FMO2 32 and PAX6 , which may mediate AD-relevant pathways in epithelial-to-mesenchymal transition 33,34 (Fig. S13G-I).…”
Section: Resultsmentioning
confidence: 99%
“…14,15 As a result, epithelial markers such as E-cadherin are decreased, whereas mesenchymal markers including vimentin and fibroblast-specific protein 1 (FSP1) are increased, contributing to airway remodeling. 16,17 Inhibition of the EMT ameliorates ovalbumin-induced airway remodeling in mice. 18 Recent evidence has shown that the EMT reduces the expression of anti-inflammatory genes induced by glucocorticoids in human lung epithelial cells, causing steroid insensitivity, and is related to refractory asthma.…”
Section: Introductionmentioning
confidence: 99%